The Size and Contribution of the Informal Economy in Jordan during the Period 2019-2023 - Abu Al-Sondos, Jihad Ahmad (Journal of Economic, Administrative and Legal Sciences, 2025)
The Paper aims to analyze the reality of the informal economy in Jordan, estimate the size and distribution of labor force by economic activity, and its contribution to the gross domestic product (GDP).The labor force statistics method was used to estimate the size of the informal economy, the total national labor force, the rate of economic participation in the formal economy, the percentage of decline in the officially estimated labor force (employed and unemployed) relative to the total national labor force, and the total labor force in the informal economy. The study estimated its contribution to the GDP relative to the formal economy's contribution to the GDP.The most important results of the Paper were an estimate of the national labor force in Jordan in 2023 at approximately 2,532,082 million workers, distributed at a rate of 61.4% in the formal economy and 38.6% in the informal economy. The number of workers in the informal economy reached approximately 976,850, with Jordanian workers 63.4% and non-Jordanian workers 36.6%.The contribution of the informal economy was estimated at approximately JOD 9.766 billion, representing 26.9% of the gross domestic product (GDP) at current prices in 2023. The value of taxes due to the state was estimated at JOD 1.4 billion annually, representing 14.1% of total taxes on production.The paper recommended to expand social safety nets for Jordanian workers, supporting and simplifying procedures for their integration into the formal economy.
Keywords: Informal economy; informal labor; gross domestic product; economic participation